2006
DOI: 10.1108/09654280610637175
|View full text |Cite
|
Sign up to set email alerts
|

How is your walking group running?

Abstract: Purpose -The present study sought to obtain a better understanding of the determinants that influence the adherence to individual walking groups. Design/methodology/approach -The study took place as part of the "Just Walk It" (JWI) programme of the Australian National Heart Foundation. The research model incorporated social environmental, physical environmental, cognitive and socio-demographic factors. Participants (n ¼ 284; response rate 49.6 per cent) of the JWI programmme completed a survey, which measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 21 publications
(34 reference statements)
2
31
1
2
Order By: Relevance
“…Group walking is a potentially attractive physical activity intervention that has particular potential to engage those who are interested in the outdoors, whether for leisure or as a health intervention and has been found to be cost-effective in increasing physical activity 17. Additionally, the dynamics and social cohesion of walking groups may have supportive effects that encourage and sustain adherence and positive attitudes towards physical activity,18 companionship and a shared experience of wellness 19. A systematic review in 2007 by Ogilvie et al 20 concluded that people could be encouraged to walk more if interventions were tailored to their needs and targeted at the most sedentary or at those most motivated to change and that group-based approaches, such as the social support of walking groups, are one method of delivering this.…”
Section: Introductionmentioning
confidence: 99%
“…Group walking is a potentially attractive physical activity intervention that has particular potential to engage those who are interested in the outdoors, whether for leisure or as a health intervention and has been found to be cost-effective in increasing physical activity 17. Additionally, the dynamics and social cohesion of walking groups may have supportive effects that encourage and sustain adherence and positive attitudes towards physical activity,18 companionship and a shared experience of wellness 19. A systematic review in 2007 by Ogilvie et al 20 concluded that people could be encouraged to walk more if interventions were tailored to their needs and targeted at the most sedentary or at those most motivated to change and that group-based approaches, such as the social support of walking groups, are one method of delivering this.…”
Section: Introductionmentioning
confidence: 99%
“…13, 14 Such interventions have used a wide range of strategies to influence the group environment, process, and structure to increase cohesion among members. While the mechanisms underlying intervention effectiveness are poorly understood, studies have shown that group cohesion is positively associated with physical activity outcomes, including intervention adherence, 1519 physical activity, 2022 and cardio respiratory fitness. 23 Group cohesion in the physical activity context has been defined as a construct that includes the following dimensions: individual attraction to the group task (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence is particularly high in people in cohesive groups 27) . Similarly, in walking groups, social cohesion may be a predictor of adherence to the walking group 30) . Among the various aspects of social support, material support and positive social interaction had the largest potential to promote adherence to group exercise 31) .…”
Section: Mechanisms Between Group Exercise and Health Outcomementioning
confidence: 99%